Innovative Approaches and Methods in Teaching Technical Subjects - et. al., K.J. Rustamov, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
: Relevance. In the learning process, it is necessary to pay attention, first of all, to those methods in which listeners identify themselves with the educational material, are included in the studied situation, are encouraged to take active actions, experience a state of success and accordingly motivate their behavior. Aim. The purpose of our experimental study was to determine the possibility and effectiveness of using active and interactive forms in teaching technical disciplines. Methods. Scientific methods were applied such as working with documents, comparative analysis, literature review, questionnaires, statistics, etc. Results. In the results of experimental work, the indicators of students are given for three years in three subjects: theoretical mechanics, practical mechanics and modelling. Conclusion. In the conclusion, conclusions are given on this topic.